O direito à cidade como instrumento de pacificação social: dos estudos criminológicos da Escola de Chicago aos princípios e diretrizes urbanísticos brasileiros - COSTA, Breno Patrick Pereira (2023)
The aim of this work, from the theoretical perspective developed by the Chicago Criminological and Sociological School and also by the guidelines and guiding principles of Urban Law, is to analyze how the spatial configuration of cities can be an inhibiting or enhancing factor of criminal activity, the depending on their level of social and urban organization. Sequentially, based on studies by Brazilian researchers, an attempt is made to ascertain the relevance of the interrelation between social disorganization, urban disorganization and the high occurrence of criminal practices in certain areas, which leads to the following problematization: By guaranteeing the right to the city - access to a well-structured city with quality services, which observe fundamental rights - is the State providing population well-being and social pacification? Finally, legal predictions and practices will be studied, based on the Brazilian Constitution and current legislation, on the development of public policies aimed at the urban environment, as a way of making social peace possible within the different areas of cities. The research method used was strictly bibliographical research and, based on the theoretical research, it was possible to understand and identify the territorial and social factors that stimulate negative attitudes and criminal practices, as in the Chicago School's theory of social disorganization, presented by Prado and Maillo (2013) and also the measures that were and can be taken at the constitutional level presented mainly by Bordalo (2022) and by Saule Jr and Libório (2021), and also social as those presented mainly by Alfonsin and Lanfredi (2021 ).